The Beloved Eyewitness - van de Weghe, Luuk (New Testament studies, 2022)
In 1963, New Testament Studies published an article by Pierson Parker in which he argued that the commonalities of the Third and Fourth Gospels result from direct contact between their respective authors. This article strengthens Parker's case. It highlights additional patterns of commonality between the two Gospels. It demonstrates that these areas of commonality align with events in the Fourth Gospel allegedly experienced by the Beloved Disciple. It considers the best explanation of this phenomenon.